Exploring the Earth Summit : findings of the Rio United Nations Conference on Environment and Development : implications for South Africa - Wynberg, Rachel (Department of Environmental and Geographical Science, 2024)
In a collective bid to safeguard the Earth, almost 50 000 people gathered in Rio de Janeiro in June 1992 for what has been described as the inception of the "Environmental Revolution. " Among them were 103 heads of state, 9 000 journalists, a range of governmental delegations and non-governmental organisations, indigenous peoples, women's groups, youth and children, trade unions, business and industry, academics, religious groups and concerned individuals.